If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 = 8p + -1(33 + -2p) -18 = 8p + (33 * -1 + -2p * -1) -18 = 8p + (-33 + 2p) Reorder the terms: -18 = -33 + 8p + 2p Combine like terms: 8p + 2p = 10p -18 = -33 + 10p Solving -18 = -33 + 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. -18 + -10p = -33 + 10p + -10p Combine like terms: 10p + -10p = 0 -18 + -10p = -33 + 0 -18 + -10p = -33 Add '18' to each side of the equation. -18 + 18 + -10p = -33 + 18 Combine like terms: -18 + 18 = 0 0 + -10p = -33 + 18 -10p = -33 + 18 Combine like terms: -33 + 18 = -15 -10p = -15 Divide each side by '-10'. p = 1.5 Simplifying p = 1.5
| -8f=-184 | | 11x+11=10x-21 | | A^2-4A+4=0 | | 16(2x-5)=4(8x+8) | | 36-(5a+19)=-3 | | 9x-12=8x+2 | | 12y=6y+9 | | 0=-9m-18 | | 7+13s-2=9s+25-6s | | m-(4+2m)+3=2m+2 | | -6x+8=62 | | P^2+6=127 | | -107+k=-99 | | 12x+29=3x+254 | | x^4+2x^2=3x | | -16=y-25 | | 4y+11y=120 | | 102-6x=12x+20 | | [2x-3]=6 | | 28-k=-19 | | k-49=-62 | | 13-7x=88-42x | | (x)(6)=-30 | | 19-2x=5-10x | | -14t+7=49 | | -11.1x=77.7 | | 4x-f=-22 | | x-8.1=-3.7 | | -9(3b+2)+(28b-2)=0 | | -5-4+q=12 | | p^3+7p-6=0 | | 4s^2+8s=221 |